Modeling on “Alphabet” of Jovian S-Bursts - Arkhipov, A.V. (Радиофизика и радиоастрономия, 2002)
It is shown that the typical elements of complex S-bursts in dynamic spectra of Jovian decametric radio emission ("alphabet") could be explained by propagation delay of radiation due to helicoidal trajectory of S-emitter.